Analisis Kualitas Kecap Manis Instan dari Daging Sapi Tetelan - Ambar Fidyasari, Rini Rahayu Sihmawati Dwi Agustiyah Rosida (AGROKNOW, 2013)
Abstract. This study aimed to determine the effect of the concentration of the enzyme papain (E) and incubation time (T) on the quality of the âtetelanâ beef sauce. The research was conducted in June 2010 at the Faculty of Food Industry University of 17 Agustus 1945 Surabaya. The method used is an experimental method using a randomized block design (RBD) factorial pattern that consists of two factors. The first factor is the addition of papain enzyme concentration (E) with level E1 = 7.5% w/w, E2 = 12.5% w/w and E3 = 17.5% w/w. The second factor is the incubation time (T) with a standard T1 and T2 = 24 hours and 48 hours. Observed data include: Water content, water activity (Aw) and protein levels.The results showed variations in the concentration of the papain enzyme and incubation time on making soy âtetelanâ beef there are very real differences in the influence of the protein content. Highest protein content in E3T2 treatment is 4.080%, and lowest in E1T1 treatment is 2.163%. Treatment E1T1 to E3T2 treatment meets quality standards soy sauce, if viewed from the protein content, as a minimum protein content is 2%. Judging from the value of nutrition and food preservation E3T2 treatment is the best treatment for a higher protein content (4.080%), moisture content and water activity (Aw) was lower (2.057%, 0.685%).Kata Kunci : Enzim, Mutu kecap daging sapi tetelanÂ